Investigating the Effect of TOEFL® Preparation Training on English Proficiency of Grade 12 Students at MAN 1 Tangerang - Lastari, Dyah Supraba; Nargis, Nargis; Firdaus, Moh. Iqbal (English Education and Literature Journal (E-Jou), 2025)
English proficiency plays a crucial role for senior high school students, particularly in preparing for higher education and entering the workforce. One of the most widely administered standardized tests to measure English proficiency is TOEFL (Test of English as a Foreign Language) and often serves as a requirement for university admission. The aim of this study was to examine the effect of TOEFL preparation training on the English proficiency of 12th-grade students at MAN 1 Tangerang. A quasi-experimental method was implemented by using a one-group pretest-posttest design. The training program material covered skills assessed in TOEFL PBT (Paper Based test), namely listening, structure and written expressions and reading. The researchers conducted a pre-test and a post-test to measure students’ English proficiency improvement. The findings of the study showed a significant difference between the pre-test and post-test results. This indicates that the TOEFL preparation training effectively improved students' English proficiency. The significance of this study is reflected in its role in developing to English language instruction at secondary schools, especially in Madrasah contexts. The educational implications suggest that integrating TOEFL preparation programs into school curricula can strengthen students’ readiness for academic challenges and improve their chances of success in university entrance processes